Ccdc80-l1 Is involved in axon pathfinding of zebrafish motoneurons. - Chiara Brusegan; Anna Pistocchi; Andrea Frassine; Isabella Della Noce; Filippo Schepis; Franco Cotelli (PLoS ONE)
Axon pathfinding is a subfield of neural development by which neurons send out axons to reach the correct targets. In particular, motoneurons extend their axons toward skeletal muscles, leading to spontaneous motor activity. In this study, we identified the zebrafish Ccdc80 and Ccdc80-like1 (Ccdc80-l1) proteins in silico on the basis of their high aminoacidic sequence identity with the human CCDC80 (Coiled-Coil Domain Containing 80). We focused on ccdc80-l1 gene that is expressed in nervous and non-nervous tissues, in particular in territories correlated with axonal migration, such as adaxial cells and muscle pioneers. Loss of ccdc80-l1 in zebrafish embryos induced motility issues, although somitogenesis and myogenesis were not impaired. Our results strongly suggest that ccdc80-l1 is involved in axon guidance of primary and secondary motoneurons populations, but not in their proper formation. ccdc80-l1 has a differential role as regards the development of ventral and dorsal motoneurons, and this is consistent with the asymmetric distribution of the transcript. The axonal migration defects observed in ccdc80-l1 loss-of-function embryos are similar to the phenotype of several mutants with altered Hedgehog activity. Indeed, we reported that ccdc80-l1 expression is positively regulated by the Hedgehog pathway in adaxial cells and muscle pioneers. These findings strongly indicate ccdc80-l1 as a down-stream effector of the Hedgehog pathway.